CEPROTAN TRADITIONAL CEREMONY PROCESSION IN BATIK MOTIFS FOR CASUAL CLOTHES - Ningsih, Nadia Puspita; Lestari, Rizki (Runtas: Jurnal Fesyen dan Wastra Nusantara, 2023)
Ceprotan traditional ceremonial procession, Sekar Village, Pacitan Regency is a tradition that contains many cultural, social, artistic and economic values. The final project of this work aims to describe ideas and create casual clothing by applying the ceprotan traditional ceremonial procession motif as the basic idea in creating works with an aesthetic approach. The scope of the Ceprotan traditional ceremonial procession gave rise to ideas to be developed into the creation of batik motifs. The process of creating works starts from the exploration stage, namely witnessing the procession of the Ceprotan traditional ceremony which is then poured into the design stage of batik motif designs on casual clothing . The last stage is the embodiment stage, in this process starting from making dress patterns, cutting, coloring cloth, pelorodan , producing, sewing to finishing. The technique used in the process of creating works is the dab and wipe technique. The materials and tools used are candles, canting, remasol, silk cotton fabrics, lurik fabrics, brocade fabrics and organza fabrics. The results of the work amounted to 5 clothes. Each work is titled according to the procession, namely work 1 entitled Balangan Cengkir, work 2 entitled Kirab Panjang Ilang, work 3 entitled Tabur Sekar, work 4 entitled Arak-arakan Jolen, and work 5 entitled Arak-arakan cengkir. This design resulted in an innovation to preserve the traditional Ceprotan ceremonial tradition and batik art in the fashion sector .